Nanostructure-Polymer Composites for Soft-Tissue Engineering - Atiqah A.; Ansari M.N.M. (Elsevier, 2023)
There are various applications for nanostructure polymers, and most of these applications are still in their infancy but show huge potential. Nanostructure-polymer composites can be fabricated by several techniques, for instance, electrospinning, template synthesis, phase separation, drawing, and self-assembly. Nanostructured polymer composites can be created to obtain superior biological, physical, mechanical, and electrical characteristics. This review addresses the most current developments in the field of biomedicine, in particular soft-tissue engineering. Additional studies to are required, however in this chapter we discuss the materials and manufacturing of nanostructured composites, their weaknesses, and outline the future direction in developing more advanced nanocomposites structured for soft-tissue engineering applications. 2019 Elsevier Inc. All rights reserved.